The Effect of State-Owned Asset Management on the Quality of Financial Statements at the State Audit Agency - Pandji Oetomo; Elsa Imelda (Journal of Economics and Business UBS, 2026)
The quality of government financial statements is a key indicator of transparency, accountability, and effective public financial management. One of the principal factors influencing the quality of financial statements is the proper administration of Barang Milik Negara (BMN; State Property), which includes bookkeeping, inventory, and reporting processes. Inadequate BMN administration may result in inaccurate asset records, discrepancies between administrative records and physical assets, and reduced reliability of financial information. This study aims to examine the effect of BMN administration, comprising bookkeeping, inventory, and reporting, on the quality of financial statements at the Audit Board of the Republic of Indonesia (BPK RI). This research employed a quantitative approach with an associative research design. The population consisted of employees involved in BMN administration at BPK RI, and 61 respondents were selected using purposive sampling. Data were collected through a questionnaire using a five-point Likert scale and analyzed using multiple linear regression with IBM SPSS Statistics. The results indicate that BMN bookkeeping, inventory, and reporting each had a significant positive effect on the quality of financial statements. Simultaneously, the three components of BMN administration significantly influenced financial statement quality, with an R² value of 0.565, indicating that 56.5% of the variation in financial statement quality was explained by BMN administration. The findings demonstrate that effective BMN administration plays a critical role in enhancing the accuracy, reliability, and accountability of government financial reporting. This study concludes that strengthening BMN administration systems is essential for supporting sustainable public sector governance and enhancing institutional accountability.